2021
DOI: 10.1002/wps.20883
|View full text |Cite
|
Sign up to set email alerts
|

The growing field of digital psychiatry: current evidence and the future of apps, social media, chatbots, and virtual reality

Abstract: As the COVID-19 pandemic has largely increased the utilization of telehealth, mobile mental health technologies -such as smartphone apps, virtual reality, chatbots, and social media -have also gained attention. These digital health technologies offer the potential of accessible and scalable interventions that can augment traditional care. In this paper, we provide a comprehensive update on the overall field of digital psychiatry, covering three areas. First, we outline the relevance of recent technological adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
380
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 545 publications
(399 citation statements)
references
References 225 publications
(271 reference statements)
6
380
0
13
Order By: Relevance
“…Indeed, innovations are more easily adopted when their required procedural knowledge is codified and when access to high-quality training and fidelity-based supervision is available ( 43 , 52 ). Clarifying the role of VR within the clinical workflow, the ongoing need for clinical skill (e.g., assessment, psychoeducation, monitoring) in providing access to VR-based interventions, as well as the potential consumer benefits, may also alleviate identified workforce concerns by reinforcing professional values, including altruistic motivations to help patients ( 21 , 47 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, innovations are more easily adopted when their required procedural knowledge is codified and when access to high-quality training and fidelity-based supervision is available ( 43 , 52 ). Clarifying the role of VR within the clinical workflow, the ongoing need for clinical skill (e.g., assessment, psychoeducation, monitoring) in providing access to VR-based interventions, as well as the potential consumer benefits, may also alleviate identified workforce concerns by reinforcing professional values, including altruistic motivations to help patients ( 21 , 47 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Virtual reality allows consumers to receive medical therapies or instruction as actively participating in an elevated, dynamic, and individualized virtual world, rather than as inert spectators. 52 Statistical findings of our study reported that virtual reality fitness has a positive role in behavior and attitude management during the COVID-19 pandemic isolation. Similar results reported in many studies and state that virtual reality exercise has been acknowledged as a new way to encourage strength training and healthy behaviors in recent years.…”
Section: Discussionmentioning
confidence: 66%
“…The high prevalence of anxiety “vastly exceeds the capacities of mental health services,” and this gap has only increased over the past several years [ 75 ]. App-based digital therapeutics offer a viable and practical route toward augmenting traditional mental health care and, in some cases, serve as a first-line treatment [ 76 ]. For example, if a patient in a primary care clinic screens positive for anxiety, an evidence-based digital therapeutic such as the one described in this study can be offered as an augmentation to standard medication treatment, or in some cases, it can be offered if a trial of medications has yielded suboptimal results or if a patient is not interested or willing to try a medication as an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…As integrative care models (eg, embedding psychiatric or psychological services within primary care clinics) gain momentum, one of the primary limitations is the cost and availability of trained therapists. However, because 85% of the US population has a smartphone, digital therapeutics may be able to serve as the mobile component of an integrative care clinic at a low cost, filling in for the lack of physical space and trained mental health clinicians [ 76 ]. In addition, in corporate settings where employers are increasingly aiming to meet the mental health needs of employees, it may be possible to quickly and confidentially deploy evidence-based digital therapeutics to help employees with mild or moderate anxiety.…”
Section: Discussionmentioning
confidence: 99%